The geology of the Proterozoic Haveri Au-Cu deposit, Southern Finland - Strauss, Toby Anthony Lavery (Rhodes University, Faculty of Science, Department of Geology, 2004)
The Haveri Au-Cu deposit is located in southern Finland about 175 km north of Helsinki. It occurs on the northern edge of the continental island arc-type, volcano-sedimentary Tampere Schist Belt (TSB) within the Palaeoproterozoic Svecofennian Domain (2.0 "“ 1.75 Ga) of the Fennoscandian Shield. The 1.99 Ga Haveri Formation forms the base of the supracrustal stratigraphy consisting of metavolcanic pillow lavas and breccias passing upwards into intercalated metatuffs and metatuffites. There is a continuous gradation upwards from the predominantly volcaniclastic Haveri Formation into the overlying epiclastic meta-greywackes of the Osara Formation. The Haveri deposit is hosted in this contact zone. This supracrustal sequence has been intruded concordantly by quartz-feldspar porphyries. Approximately 1.89 Ga ago, high crustal heat flow led to the generation and emplacement of voluminous synkinematic, I-type, magnetite-series granitoids of the Central Finland Granitoid Complex (CFGC), resulting in coeval high-T/low-P metamorphism (hornfelsic textures), and Dâ‚ deformation. During the crystallisation and cooling of the granitoids, a magmatic-dominated hydrothermal system caused extensive hydrothermal alteration and Cu-Au mineralisation through the late-Dâ‚ to early-Dâ‚‚ deformation. Initially, a pre-ore Na-Ca alteration phase caused albitisation of the host rock. This was closely followed by strong Ca-Fe alteration, responsible for widespread amphibolitisation and quartz veining and associated with abundant pyrrhotite, magnetite, chalcopyrite and gold mineralisation. More localised calcic-skarn alteration is also present as zoned garnetpyroxene- epidote skarn assemblages with associated pyrrhotite and minor sphalerite, centred on quartzcalciteÂ± scapolite veinlets. Post-ore alteration includes an evolution to more K-rich alteration (biotitisation). Late Dâ‚‚-retrograde chlorite began to replace the earlier high-T assemblage. Late emanations (post-Dâ‚‚ and pre-Dâ‚ƒ) from the cooling granitoids, under lower temperatures and oxidising conditions, are represented by carbonate-barite veins and epidote veinlets. Later, narrow dolerite dykes were emplaced followed by a weak Dâ‚ƒ deformation, resulting in shearing and structural reactivation along the carbonate-barite bands. This phase was accompanied by pyrite deposition. Both sulphides and oxides are common at Haveri, with ore types varying from massive sulphide and/or magnetite, to networks of veinlets and disseminations of oxides and/or sulphides. Cataclastites, consisting of deformed, brecciated bands of sulphide, with rounded and angular clasts of quartz vein material and altered host-rock are an economically important ore type. Ore minerals are principally pyrrhotite, magnetite and chalcopyrite with lesser amounts of pyrite, molybdenite and sphalerite. There is a general progression from early magnetite, through pyrrhotite to pyrite indicating increasing sulphidation with time. Gold is typically found as free gold within quartz veins and within intense zones of amphibolitisation. Considerable gold is also found in the cataclastite ore type either as invisible gold within the sulphides and/or as free gold within the breccia fragments. The unaltered amphibolites of the Haveri Formation can be classified as medium-K basalts of the tholeiitic trend. Trace and REE support an interpretation of formation in a back-arc basin setting. The unaltered porphyritic rocks are calc-alkaline dacites, and are interpreted, along with the granitoids as having an arc-type origin. This is consistent with the evolution from an initial back-arc basin, through a period of passive margin and/or fore-arc deposition represented by the Osara Formation greywackes and the basal stratigraphy of the TSB, prior to the onset of arc-related volcanic activity characteristic of the TSB and the Svecofennian proper. Using a combination of petrogenetic grids, mineral compositions (garnet-biotite and hornblendeplagioclase thermometers) and oxygen isotope thermometry, peak metamorphism can be constrained to a maximum of approximately 600 Â°C and 1.5 kbars pressure. Furthermore, the petrogenetic grids indicate that the REDOX conditions can be constrained at 600Â°C to log f(Oâ‚‚) values of approximately - 21.0 to -26.0 and -14.5 to -17.5 for the metasedimentary rocks and mafic metavolcanic rocks respectively, thus indicating the presence of a significant REDOX boundary. Amphibole compositions from the Ca-Fe alteration phase (amphibolitisation) indicate iron enrichment with increasing alteration corresponding to higher temperatures of formation. Oxygen isotope studies combined with limited fluid inclusion studies indicate that the Ca-Fe alteration and associated quartz veins formed at high temperatures (530 "“ 610Â°C) from low COâ‚‚, low- to moderately saline (<10 eq. wt% NaCl), magmatic-dominated fluids. Fluid inclusion decrepitation textures in the quartz veins suggest isobaric decompression. This is compatible with formation in high-T/low-P environments such as contact aureoles and island arcs. The calcic-skarn assemblage, combined with phase equilibria and sphalerite geothermometry, are indicative of formation at high temperatures (500 "“ 600 Â°C) from fluids with higher COâ‚‚ contents and more saline compositions than those responsible for the Fe-Ca alteration. Limited fluid inclusion studies have identified hypersaline inclusions in secondary inclusion trails within quartz. The presence of calcite and scapolite also support formation from COâ‚‚-rich saline fluids. It is suggested that the calcic-skarn alteration and the amphibolitisation evolved from the same fluids, and that P-T changes led to fluid unmixing resulting in two fluid types responsible for the observed alteration variations. Chlorite geothermometry on retrograde chlorite indicates temperatures of 309 "“ 368 Â°C. As chlorite represents the latest hydrothermal event, this can be taken as a lower temperature limit for hydrothermal alteration and mineralisation at Haveri.The gold mineralisation at Haveri is related primarily to the Ca-Fe alteration. Under such P-T-X conditions gold was transported as chloride complexes. Ore was localised by a combination of structural controls (shears and folds) and REDOX reactions along the boundary between the oxidised metavolcanics and the reduced metasediments. In addition, fluid unmixing caused an increase in pH, and thus further augmented the precipitation of Cu and Au. During the late Dâ‚‚-event, temperatures fell below 400 Â°C, and fluids may have remobilised Au and Cu as bisulphide complexes into the shearcontrolled cataclastites and massive sulphides. The Haveri deposit has many similarities with ore deposit models that include orogenic lode-gold deposits, certain Au-skarn deposits and Fe-oxide Cu-Au deposits. However, many characteristics of the Haveri deposit, including tectonic setting, host lithologies, alteration types, proximity to I-type granitoids and P-T-X conditions of formation, compare favourably with other Early Proterozoic deposits within the TSB and Fennoscandia, as well as many of the deposits in the Cloncurry district of Australia. Consequently, the Haveri deposit can be seen to represent a high-T, Ca-rich member of the recently recognised Fe-oxide Cu-Au group of deposits.
Keywords: Geology, Stratigraphic -- Precambrian; Geology, Stratigraphic -- Proterozoic; Ore deposits -- Finland; Geology -- Finland